Women characters in Sifiso Nyathi’s play God of Women, and William Shakespeare’s Othello: A comparative exploration (Journal for Studies in Humanities and Social Sciences, 2014)
This paper compares the depictions of women characters in the plays God of Women written by Sifiso Nyathi (a famous Namibian playwright) and Othello by William Shakespeare, respectively. The two playwrights were purposely chosen on the basis that Nyathi (a Black playwright) writes in the 20th century, in Namibia, a country in Southern Africa, while Shakespeare (a White playwright) wrote in the 17th century, in England, Europe. Despite the racial differences and epochs in which the playwrights have lived and written, the paper revealed that, generally, both Nyathi and Shakespeare use a gender-bias style of writing in depicting women characters in their plays. Nyathi’s depictions portray women as sex objects for their husband’s sexual pleasures in a polygamous marriage, and also as exchange material for wealth. Women also have been portrayed as destitutes who have to stay in subservient conditions at the mercy of their husbands despite the physical and emotional abuse they endure. Shakespeare also portrays women characters negatively as dependent on their fathers in Othello. He portrays women characters as sex goddesses who would compel men to murder their women out of immense worshipping-kind of love for them. Conversely, Nyathi and Shakespeare depict women as intelligent and rational thinkers, as we see Desdemona in Othello defending her position in her choice for Othello before her father. In God of Women the wives of Chief Lewanika embrace MaInonge in solidarity of the oppressed sisters when she collapses after Joyce reveals her secret that she had a son out of wedlock with Chief Lewanika. The analysis concluded that both Nyathi and Shakespeare largely portray women characters negatively in their works, albeit in different ways that are typical of the cultures and epochs in which the authors lived. The analysis also revealed that both Nyathi and Shakespeare make use of literary devices such as foregrounding, metaphors and similes to enliven their plays and to appeal for their audiences’ entertainment.